Perbandingan Financial Distress PT Sentra Food Indonesia Tbk dan PT Garudafood Putra Putri Jaya Tbk pada Periode 2020–2022 - Wiliandika, Hapid; Muhairoh, Anita (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to compare the level of financial distress between PT Sentra Food Indonesia Tbk and PT Garudafood Putra Putri Jaya Tbk during the 2020–2022 period. The research addresses a key issue in corporate financial management early detection of bankruptcy risk especially in the food and beverage industry, which has shown both resilience and vulnerability in the post-pandemic era. A quantitative approach is employed using secondary data derived from audited financial statements published by the Indonesia Stock Exchange (IDX). The analysis utilizes financial ratio analysis and the Altman Z-Score model, which integrates five financial indicators working capital, retained earnings, earnings before interest and taxes, market value of equity, and sales relative to total assets. The results indicate a significant contrast between the two firms: PT Sentra Food Indonesia Tbk consistently recorded Z-Scores below 1.81, placing it in the distress zone with a declining financial trend, while PT Garudafood Putra Putri Jaya Tbk improved from the grey zone (Z = 2.05 in 2020) to a safe financial condition (Z > 5.00 in 2021 and 2022). These findings provide critical insights for investors, managers, and stakeholders to assess the financial viability and strategic positioning of firms within the sector. The study also reinforces the Altman Z-Score’s relevance as a practical tool for predicting corporate financial health.